O processo de aquisição de habilidades motoras convencionais em indivíduos com baixa visão - Dias, Vera Felicidade (2012)
The development process varies in terms of velocity and each individual can show delays or advances, depending on the organic, task and environment constraints of the individual (HAYWOOD, 2004). Thus, delays or advances influence directly on daily life skills, as walking, run, jump and throw. All individuals may show advances or delays in their levels of development, what also apply for those individuals with visual impairment (low vision). The aim of this study was to analyze the effect of an intervention program, in 10 individuals of both gender, aged between 6 and 12 years (mean age 9±1,7) with low vision, which were enrolled in the CAEDVs and AEE of public schools in Maringá. Medical records, children enrollment form from schools and TGMD-2 test (ULRICH, 2000) were used to evaluate all children. All students were evaluated at the beginning and end of the program with 32 sessions, built especially for the desired stimulation. Results were significant for variables such as horizontal jump (p=0,01) and stationary dribble (p=0,01), which means that the intervention improved the overall performance in 19,7%. However, despite the significant results in the motor quotient (p≤0,04), this came from very poor to poor. Thus, due to indicator of improvement found, it is possible to conclude that with a process of regular stimulation, it can be possible to supply the needs of these individuals as soon as promote their autonomy.